Six seconds to talk back: The emergence of racial comedy as a sociopolitical discourse genre on Vine - Calhoun, Kendra Nicole (AoIR Selected Papers of Internet Research, 2016)
In this paper I analyze how a new discourse genre has emerged on the video-based social media platform Vine as a result of its technological affordances (Hutchby 2001) for video production and dissemination. “Vine racial comedy” is a form of comedic performance that functions as a sociopolitical discourse genre by addressing issues of race in the United States within the 6-second time limit of each video. Pioneered by King Bach, a 28-year-old African-American male who is the most-followed person on Vine (15.1 million followers), this genre of Vine comedy challenges the sociopolitical status quo in the tradition of Black stand-up comedy (Rahman 2004), including stylistic use of non-standard language varieties (e.g., African American English) and critical engagement with cultural stereotypes (Carpio 2008). The auditory and visual semiotic features of King Bach's comedy have become markers of genre now that they have been adopted by popular Latino, Arab, East Asian and other Viners of color. Vine racial comedy is significant as both an innovative online discourse genre and a new iteration of using social media to “talk back” to mainstream media (cf. Bonilla & Rosa 2015) that often ignores or misrepresents racial issues (Cottle 2000). Vine and its affordances have created a space in which this social media performer can use comedy to direct the attention of his millions of followers to sociopolitical issues they might otherwise ignore.